Penggunaan aplikasi Assemblr Edu untuk meningkatkan motivasi belajar IPAS peserta didik kelas IV sekolah dasar - Paras Awignamastu; Karsono Karsono; Peduk Ritayanti (Universitas Sebelas Maret, 2024)
The research objectives include: 1) Increasing learning motivation in science subjects using the Assemblr Edu application; and 2) Knowing how to use the Assemblr Edu application which can increase learning motivation in science subjects. This research is of the type Classroom Action Research (CAR). Each cycle contains planning, action, observation and reflection. The research subjects consisted of 14 4th grade students with 7 girls and 7 boys as well as the homeroom teacher. Obtaining data through observation, interviews, and questionnaires. Data analysis uses triangulation techniques with the Miles and Huberman model. Based on the results questionnaires, an increase in students' science learning motivation was shown by an average initial pre-action of 61%. Then after carrying out the actions in cycle I the average motivation rose to 73% and after the actions in cycle II the average became 84%.